Pengembangan Potensi Obyek Wisata Goa Kreo Semarang Di Masa Pandemi Covid-19 - Danang Indarto; Waskito Waskito; Siti Nurindah Sari (Indonesian Journal of Geography Education, 2021)
Strategy for Development of Tourism Potential of Goa Kreo Semarang in the Pandemic Period. Thesis. Geography Education Study Program. Faculty of Teacher Training and Education. Ivet University. The city of Semarang itself has the potential for tourism objects that need to be studied in depth to be developed in the future, including the Kreo Cave tourism object which is located in Kandri village, Gunungpati district. This Kreo Cave tourism object is a leading tourism product in the city of Semarang with the highest level of visits every year compared to the level of visits to other tourist objects in Semarang. Goa Kreo has a very attractive potential and attraction because around Goa Kreo there is a vast expanse of rice fields, steep cliffs full of trees, including rare trees and a clear rocky river so as to create a beautiful panorama. The development of the right tourism potential can make Goa Kreo an attractive tourist destination to visit. The development of the Covid-19 virus has had a major impact on various fields, one of which is the tourism sector. During the Covid-19 pandemic, tourism activities were more limited and it was necessary to implement the health protocols that had been determined by the Semarang City government. This study aims to find out how the strategy for developing the tourism potential of Goa Kreo Semarang during the pandemic period is and what factors and obstacles that influence it. This research is a qualitative descriptive study. Data collection techniques used in this study were observation techniques, interview techniques, and documentation techniques. The interview technique was conducted with 3 sources. The data were then analyzed using qualitative descriptive methods and tested for data quality using source and triangulation techniques. The results showed that the right strategy in developing the Kreo Cave Tourism object was to build an integrated tourism industry during the pandemic which attracted tourists to come to the city of Semarang. Expand and improve tourism marketing efforts so that tourists can obtain complete information about Kreo Cave tourism objects so that they can attract tourists to come to Kreo Caves. Conducting outreach to the community in particular and the people of the city of Semarang in an effort to maintain cleanliness and apply health protocols to increase the potential of Kreo Cave tourism objects during the pandemic. Therefore, the manager of Goa Kreo tourism objects, especially the Semarang City Tourism and Culture Office, always tries to continue to develop Goa Kreo tourism objects, especially during this pandemic.